Assessment of Post-traumatic Growth using Post-traumatic Growth Inventory and the Impact of Clinical Pharmacists on Post-Traumatic Growth Enhancement - SankarViriti, Uma (Asian Journal of Pharmaceutics (AJP), 2025)
This study aimed to evaluate the impact of trauma and assess levels of post-traumatic growth (PTG) among individuals who had experienced traumatic events. Additionally, it sought to explore the effectiveness of clinical pharmacist–led counselling in enhancing PTG levels in individuals with lower initial PTG scores. Materials and Methods: A total of 130 participants, aged between 16 to 80 years, who had experienced trauma at some point in their lives, were included in this study. A mixed-method approach was employed, incorporating both qualitative interviews and quantitative assessments. Two standardized tools were used: the Post- Traumatic Growth Inventory (PTGI) and the Impact of Event Scale-Revised (IES-R). Participants underwent two counselling sessions led by clinical pharmacists. Pre- and post-counselling PTG levels were compared. Statistical analysis was conducted using a two-way ANOVA, with a P-value < 0.05 considered statistically significant. Results and Discussion: Out of the 130 participants, 56% (73 individuals) exhibited very high levels of post-traumatic growth (PTG), while 44% (57 individuals) showed moderate PTG prior to counselling. After twosessions of clinical pharmacist-led counselling, a notable improvement was observed in PTG levels, with several participants shifting from lower to higher PTG categories. Statistical analysis using two-way ANOVA revealed significant improvements in specific domains of PTG: personal strength (P = 0.03), new possibilities (P = 0.005), appreciation for life (P = 0.04), and total PTG score (P = 0.03). However, no statistically significant changes were found in the areas of improved relationships (P = 0.127) and spiritual growth (P = 0.5). These results suggest that counselling interventions by clinical pharmacists have a meaningful impact on enhancing psychological recovery and fostering growth after trauma, particularly in areas related to personal resilience, future opportunities, and life appreciation. Conclusion: The study demonstrates that clinical pharmacists play a significant role in supporting trauma-affected individuals through structured counselling, which can enhance various aspects of post-traumatic growth. Targeted pharmacist interventions can lead to meaningful psychological improvements, especially in personal strength, new life opportunities, and overall PTG.